Educate or form the survival man? - Grochowska, Irena (Studia Ecologiae et Bioethicae, 2004)
In the modern world, man has more and more responsibilities. Integration of thought, attitude, and activities providing “wisdom of life”, which guarantees careful activities in everyday life, is not enough. In nowadays era of fast changes, it is not enough to be a mature man in a sense of human cultural behavior, the needs are greater, anticipated thought and the ability to communicate with another man is necessary. Survival of man and overcoming the ecological crisis becomes a complex problem, which should be regarded as a system, a synthesis of theory and practice in many disciplines of science. A man prepared for service to the environment is called "Survival man". The "survival man" is a term, which refers to an integrally formed personality, that has a mature personality, prepared to coexist with other creatures. The "survival man" can integrate with others, make personal contacts "beyond boundaries" and also has the feeling of their vocation and their own place in nature. In order for these necessary dispositions of modern man, to become permanent behavior that is deeply motivated, the need for long-lasting bridging up process, after which follows later shaping in order for a man to achieve readiness to serve and act in a certain area. If a man is to serve, both to himself and others, first he has to reach to the deepest layers of the inner self - from sincerity to truth, in the bring in gup process. In order to reach full awareness of his role in the world.